UNA LINGUA, TANTE LINGUE: IL PLURALISMO LINGUISTICO IN CLASSE: Contributi di Monica Barni, Gianluca Baldo, Lorenzo Zanasi, Verena Platzgummer, Olga Lopopolo, Marta Guarda, Gisela Mayr, Paola Masillo, Sabrina Machetti, Cecilia Andorno, Paolo Della Putta, Rosa Pugliese, Silvia Sordella, Greta Zanoni, Silvana Loiero (Italiano LinguaDue, 2023)
A cura di Francesca Gallina e Silvana Loiero